THE IMPACT OF EXCHANGE RATE VOLATILITY AND INFLATION ON THE NIGERIAN ECONOMY - Olabode Eric Olabisi; Kemi Funlayo AKEJU (Business & Management Compass)
In African countries, exchange rate volatility, inflation, and economic growth relationships remain debatable, especially in Nigeria, because of the historical homogeneity of the monetary macroeconomic variables among the member countries. Therefore, the purpose of this paper is to examine the relationship among exchange rate volatility, inflation, and economic growth in Nigeria from 1985 to 2022. The autoregressive distributed lag (ARDL) estimation technique of analysis was employed in achieving the objective of the study. We employed GARCH (1, 1) to obtain the volatility of the exchange rate data. Results indicated that exchange rate volatility and inflation adversely influenced the growth of the Nigerian economy. Further analysis reveals a negative impact when the interaction of exchange rate volatility and inflation is tested on growth. Also, the result revealed that gross capital formation promotes the growth of the Nigerian economy. This result confirms the positive evidence ascertained in the literature on the investment growth nexus. It is therefore recommended that policies that focus on improving local currency should be the top priority of the government. Also, policies that would reduce overdependence on foreign raw materials for production should be encouraged.